(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: Digital health holds promise for enhancing care coordination and supporting patient self-management. However, various barriers, including at the healthcare professional level, hinder its adoption. This cross-sectional study explored the eHealth profile of primary care physicians and its relationship with care coordination. METHODS: As part of “The Commonwealth Fund’s 2022 International Health Policy Survey of Primary Care Physicians in 10 Countries”, 1114 physicians in Switzerland completed a questionnaire on their sociodemographic and workplace characteristics, digital health use and care coordination practices. Based on their responses concerning the modality, frequency and application of digital health tools, we created a digital health score. Based on responses describing the collaboration with specialists and paramedical health professionals, we created a care coordination score. The associations between both scores were assessed using stratified analyses and multiple linear regression. RESULTS: Among the 1114 participants (46% women, mean age 52 years), 83% used electronic patient records, 96% used teleconsultations for less than 5% of consultations, and 63% never used connected health tools to monitor patients with chronic diseases. Further, 16% allowed online appointments, 20% online medical prescriptions, 52% the possibility of electronically communicating lists of medications with other healthcare professionals, and 89% the possibility of email or web communications with the patient. The eHealth score was positively associated with the number of weekly working hours, being an internal medicine specialist or practising physician, the number of full-time equivalents in the practice and being in a group practice setting. The higher the eHealth profile score, the higher the care coordination score. CONCLUSION: Digital health and care coordination were positively associated. This could underscore the potential benefits of digital health in enhancing collaborative and interprofessional care practices.